The challenge of communicating corporate social responsibility : the case of Coca-Cola - Laranjeiro, Beatriz Mesquita (2019)
The communication of Corporate Social Responsibility has undergone changes in recent years. It has evolved into a new paradigm of shared value between companies and society; one that suggests that it is possible for companies to engage in profitable activities which provide for benefits on a social level. Given this context, this work explores the challenges, tensions and complexities of the communication of corporate social responsibility, using The Coca-Cola Company as a case study and from a critical marketing perspective. The study involved qualitative methods of secondary and primary research based on an analysis of the company’s sustainability reports, a journalistic investigatory documentary and evidence from consumer interviews. A triangulation of the resulting data made it possible to determine the divergences and tensions between the three perspectives – company, media and consumers. This then allowed the conclusion that, although consumer perceptions of the communication of corporate social responsibility are positive, the emergence of sustainability issues in society can lead to manipulations and suggestions of unreal environmental performance, communicated through documents as sustainability reports and/or product advertisements, a situation that has attracted the attention of the media.